IMPLIKASI IMAN SEJATI DALAM PENDIDIKAN KRISTEN [IMPLICATIONS OF TRUE FAITH IN CHRISTIAN EDUCATION] - Musa Sinar Tarigan (Universitas Pelita Harapan, 2023)
AbstractChristian faith plays a very important role in education. Faith in God must affect the whole life of Christians to know God properly. This article states that the principle of true faith according to the Heidelberg Catechism is one of the important and historic documents for Christianity and its role in the field of education. The writing of this article is also to answer the various problems of understanding faith and its correlation with the field of Christian education. The discussion of this article uses literature research methods including the Bible, and various documents such as books and theological journals that discuss true faith according to the Heidelberg Catechism. The results of the discussion in this article show that true faith in God must have a very significant role in the field of holistic Christian education. Suggestions for Christian educators include being faithful to the truth and applying it in Christian education.Bahasa Indonesia AbstrakIman Kristen memiliki peran yang sangat penting dalam Pendidikan. Beriman kepada Allah harus memengaruhi seluruh kehidupan orang Kristen untuk mengenal Allah dengan benar. Artikel ini menyatakan bahwa prinsip iman sejati (true faith) menurut katekismus Heidelberg sebagai salah satu dokumen penting dan bersejarah bagi kekristenan dan bagaimana perannya dalam bidang pendidikan. Penulisan artikelini juga sebagai jawaban atas berbagai persoalan pemahaman iman dan korelasinya dengan bidang Pendidikan Kristen. Pembahasan artikel ini menggunakan metode riset literatur antara lain Alkitab, dan berbagai dokumen seperti buku, jurnal teologis yang membahas iman sejati menurut Katekismus Heidelberg. Hasil pembahasan artikel ini menunjukkan bahwa iman sejati kepada Allah harus memiliki peran yang sangat signifikan dalam bidang pendidikan Kristen yang holistis. Saran untuk para pendidik Kristen adalah untuk setia kepada kebenaran dan menerapkannya dalam pendidikan Kristen.